2005
DOI: 10.1897/04-037r.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the sorption of oxytetracycline to soils

Abstract: Veterinary antibiotics such as oxytetracycline (OTC) increasingly are found in the environment and often come into direct contact with soils via the release of animal wastes. Oxytetracycline is known to sorb strongly to soils by interaction with soil organic matter, clay minerals, and metal oxides. However, current knowledge of the influence of soil properties on OTC sorption is limited, as is our ability to predict OTC sorption to soils. This work was aimed at identifying properties that most influence the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
121
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(143 citation statements)
references
References 28 publications
(31 reference statements)
17
121
0
4
Order By: Relevance
“…7). Thus, soil solution pH is an important factor influencing the bioavailability of OTC in soil (Kulshrestha et al, 2004;Gu, 2005;Jones et al, 2005) and the transport from soil to plant. Time-dependent uptake of OTC by alfalfa showed that there was an equilibrium status of OTC uptake after 4 h (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). Thus, soil solution pH is an important factor influencing the bioavailability of OTC in soil (Kulshrestha et al, 2004;Gu, 2005;Jones et al, 2005) and the transport from soil to plant. Time-dependent uptake of OTC by alfalfa showed that there was an equilibrium status of OTC uptake after 4 h (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Denmark, concentrations of oxytetracycline ranging from 2.5 to 50 mg g À1 in soil and from 33 to 2000 mg g À1 in pig manure have been reported (Loke et al, 2002). The fate of antibiotics, including sorption and fixation, mobility and transport in soil, has been well documented (Tolls, 2001;Kulshrestha et al, 2004;Gu, 2005;Jones et al, 2005), whereas knowledge of their toxicity to plants and their uptake and transport into plants is poorly understood (Boxall et al, 2003;Thiele-Bruhn, 2003). The accumulation may or not affect the growth and development of plants; however, the uptake into plants may represent an important exposure pathway of these compounds to humans and other biota.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding mechanisms of adsorption and desorption of TCs is necessary to predict their fate and behavior in aquatic environment. Oxytetracycline (OTC), the earliest and the most widely used TCs, is an amphoteric molecule with several ionic/polar groups (Jones et al, 2005). The possible mechanisms of OTC adsorption onto sediments include the ion exchange, electrostatic forces, and surface complexation reactions (Jones et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Oxytetracycline (OTC), the earliest and the most widely used TCs, is an amphoteric molecule with several ionic/polar groups (Jones et al, 2005). The possible mechanisms of OTC adsorption onto sediments include the ion exchange, electrostatic forces, and surface complexation reactions (Jones et al, 2005). Carrasquillo et al (2008) suggested that the adjacent hydroxyl groups on OTC molecule facilitated a greater potential for surface complexation to soil metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…This cation:antibiotic interaction results in different physical properties which are environmentally relevant in many ways. Several works have reported, for instance, on the enhanced [13] or decreased [14] antibacterial properties, negative effects on soil microbial community [15] and on the sorption and mobility behaviour in soils and aquatic sediments [16,17]. Pertinent to the photoFenton process is the formation of complexes between antibiotics and Fe 2+ and Fe 3+ for two reasons.…”
Section: Introductionmentioning
confidence: 99%